Textual and Contextual Approach to Faraidh Science: A Critical Analysis in Determining The Distribution of Heritage Based on Islamic Sharia - Fitri Yuni Haryani; Hernik Khoirunnisak; Budiono Budiono (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
Islamic Inheritance law is regulated in the Qur'an in Q.S An-Nisa: 7 and An-Nisa:12. It is often regarded as a qath'i doctrine which gives no chance for ijtihad and must be accepted absolutely. The existence of the Al-Qur'an began to be challenged along with the changing times. According to liberal thinkers, Islamic inheritance law is considered a product of salaf scholars as a rule that tends to be discriminatory, for example the distribution for women who only get a half of male. The study of faraidh in fiqh books is the interpretation of scholars based on social and contextual settings where the social construction of people's lives. Thus, the provisions of the Islamic heirs need to be critically reviewed and re-analyzed by considering the contextual social development of society. This research tries to examines and observe various data sources from various books, arguments, and other written works to find out best practice of inheritance provision. This is library research in which the technique of collecting data is taken from various books, dalil, and other scientific writing. This writing is supposed to answer some critics related to inherit share for man and woman from both textual and contextual approach of faraidh.